Short-term efficacy and tolerability of lurasidone in the treatment of acute schizophrenia: A meta-analysis of randomized controlled trials. (August 2018) - Zheng, Wei; Cai, Dong-Bin; Yang, Xin-Hu; Li, Lu; Zhang, Qing-E.; Ng, Chee H.; Ungvari, Gabor S.; Li, Xian-Bin; Ning, Yu-Ping; Xiang, Yu-Tao
Abstract: Background: Lurasidone, an azapirone derivative, is a novel second generation antipsychotic with potent binding affinity for dopamine D2, serotonin 5-HT2A, 5-HT7, 5-HT1A, and noradrenaline alpha2C receptors. This updated meta-analysis of randomized controlled trials (RCTs) examined the short-term efficacy and tolerability of lurasidone in the treatment of acute schizophrenia. Methods: Double-blinded RCTs reporting on the short-term effects of lurasidone were included. Standardized mean difference (SMD) with their 95% confidence interval (CI), and number needed to harm (NNH) were computed. Results: The meta-analysis had 8 RCTs with 16 active arms that included 2373 patients with acute schizophrenia who were randomized to either lurasidone (20–160 mg/day; n = 1570) or placebo (n = 803) groups. Lurasidone was superior to placebo with regard to change in total psychopathology [SMD: -0.34, (95%CI: -0.48, -0.20), P<0.00001], positive symptoms [SMD: -0.47, (95%CI: -0.57, -0.36), P<0.00001], negative symptoms [SMD:-0.34, (95%CI: -0.45, -0.22), P<0.00001], and general psychopathology [SMD: -0.36, (95%CI: -0.48, -0.24), P<0.00001]. Results were consistent for total psychopathology in 11 out of the 13 subgroups. Lurasidone resulted in higher weight gain [SMD: 0.15, (95% CI: 0.06, 0.24), P = 0.001] and BMI [SMD: 0.17, (95%CI: 0.07, 0.28), P = 0.002] than placebo, but the differences were not clinically significant. Lurasidone group had less frequent inefficacy (NNH = 14) and discontinuation due to any reason (NNH = 17), but was associated with more frequent vomiting, akathisia, dystonia, parkinsonism, somnolence, dizziness, sedation, nausea, and weight gain of ≥7% of the initial weight (NNH = 11–50). Conclusion: This meta-analysis of 8 short-term studies supported the efficacy and safety of lurasidone in the acute phase of schizophrenia, particularly at the higher dose range of 80 mg/day. Highlights: Lurasidone, an azapirone derivative, is a novel second generation antipsychotic medication. Recent studies on efficacy and tolerability of lurasidone for acute schizophrenia was included in this meta-analysis. Lurasidone is efficacious and well-tolerated in the acute phase of schizophrenia, especially at high dose range.